Assessment of Comparative Predisposing Factors for the Production of Aflatoxins - Alizada, Mohammad Naiem (Journal of Natural Sciences – Kabul University, 2022)
Aflatoxins are secondary metabolites produced by Aspergillus flavus and Aspergillus parasiticus. Under favorable conditions, such as optimal temperature, humidity, pH, and relative humidity, these metabolites can contaminate human food and animal feed before and after harvest. Among the 20 identified aflatoxins, six (B1, B2, G1, G2, M1, and M2) are particularly significant, with aflatoxin B1 being the most harmful due to its direct link to human liver cancer. Aflatoxin contamination is common in crops such as maize, wheat, rice, and sorghum. This paper aims to review and discuss the underlying physical, nutritional, and biological factors that predispose the production of aflatoxins.